PENGARUH MODEL PEMBELAJARAN GAMIFICATION TERHADAP HASIL BELAJAR IPAS SISWA KELAS V UPTD SD NEGERI 098166 PERUMNAS - Simanjuntak, Melvin; Maria Barus; Adelina Deis Frentina Purba (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine whether there is an influence of the Gamification Learning Model on the Science Learning Outcomes of Grade V Students in Learning Light and Its Properties at UPTD SD Negeri 098166 Perumnas. There are 2 hypotheses in this study, namely (1) Alternative hypothesis (Ha), there is a significant influence of the application of the Gamification Model on the Science Learning Outcomes of Grade V Students in Learning Light and Its Properties at UPTD SD Negeri 098166 Perumnas and (2) Null hypothesis (H0), there is no significant influence of the application of the Gamification Model on the Science Learning Outcomes of Grade V Students in Learning Light and Its Properties at UPTD SD Negeri 098166 Perumnas. This research is a quantitative study with a pre-experimental design using a